Caracterização molecular e da sensibilidade a antimicrobianos de micobactérias de crescimento rápido (MCR) isoladas de pacientes submetidos a procedimentos invasivos do estado de Minas Gerais - Simone Rodrigues Ribeiro (2013)
Rapidly growing mycobacteria (RGM) are opportunistic pathogens involved mainly in infections associated with invasive procedures. Here, we have characterized RGM isolated from patients undergoing invasive procedures, from the state of Minas Gerais. Microbiological and epidemiological information were reviewed retrospectively from laboratory records. For molecular typing, PCR followed by analysis restriction fragment length of the gene hsp65 (PRA-hsp65) and Enterobacterial Repetitive Intergenic Consensus PCR (ERIC-PCR) were applied. Isolates of M. abscessus and M. chelonae were evaluated for sensitivity in vitro as recommended by the Clinical and Laboratory Standards Institute through a colorimetric assay using rezasurina. A total of 31 RGM isolated from specimens of 20 patients were recovered from the strain collection of Ezequiel Dias Foundation, between January 2007 and July 2011. The hsp65 PRA technique allowed the identification of 87.1% RGM isolates, corresponding to M. fortuitum, M. abscessus subsp. abscessus, M. abscessus subsp. bolettii, M. chelonae and M. peregrinum. Invasive surgical represented the majority of cases (60%). Among the surgery, mammaplasty was most common (50% of cases). Cases were concentrated in them Belo Horizonte (30%), Uberaba (10%), Contagem (5%), Lavras (5%), Nova Lima (5%) and Uberlândia (5%). Except for three clinical isolates of M. chelonae, different clinical isolates of RGM studied showed no epidemiological link. Four isolates showed PRA-hsp65 pattern not reported in the literature. The ERIC-PCR was useful for discriminating clinical isolates of RGM, showing a higher degree of genetic heterogeneity as compared to PRA-hsp65, but 100% genetic similarity of two clinical isolates of M. chelonae involved in an outbreak. The two isolates of M. chelonae were susceptible to amikacin, ciprofloxacin, clarithromycin, doxycycline, and sulfamethoxazole but resistant to tobramycin. All isolates of M. abscessus subsp. abscessus were sensitive to amikacin, profile showed intermediate to cefoxitin and were resistant to sulfamethoxazole. All isolates of M. abscessus subsp. bolletii were sensitive to amikacin and clarithromycin, profile showed intermediate to cefoxitin and were resistant to ciprofloxacin, doxycycline and sulfamethoxazole.